2015
DOI: 10.1364/oe.23.033588
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects of Mach-Zehnder interferometer using a liquid crystal-filled fiber

Abstract: Abstract:We demonstrated a simple and cost-effective method to fabricate all fiber Mach-Zehnder interferometer (MZI) based on cascading a short section of liquid crystal (LC)-filled hollow-optic fiber (HOF) between two single mode fibers by using automatically splicing technique. The transmission spectra of the proposed MZI with different LC-infiltrated length were measured and the temperature-induced wavelength shifts of the interference fringes were recorded. Both blue shift and red shift were observed, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As described in the previous work [19], all fiber Mach-Zehnder interferometer (MZI) can be realized by cascading a short section of liquid crystal (LC)filled hollowoptic fiber (HOF) between two single mode fibers. To study how the radicalaligned LCF affects the HOFbased MZI, the inter ference spectra of the LCFMZIs with three LC lengths: 2.2 mm, 3.0 mm, and 3.5 mm were measured as shown in figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the previous work [19], all fiber Mach-Zehnder interferometer (MZI) can be realized by cascading a short section of liquid crystal (LC)filled hollowoptic fiber (HOF) between two single mode fibers. To study how the radicalaligned LCF affects the HOFbased MZI, the inter ference spectra of the LCFMZIs with three LC lengths: 2.2 mm, 3.0 mm, and 3.5 mm were measured as shown in figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…We first developed a simple method to fabricate an allfiber MZI based on LCinfiltrated HOF with planar alignment [19]. The structure of the proposed device is constructed by splicing a LCinfiltrated HOF with length L between two stan dard singlemode fibers (SMFs) as shown in figure 1.…”
Section: Background Theory and Experimentalmentioning
confidence: 99%
“…We have developed a novel and simple technique to achieve an all-fiber MZI based on LC-filled HOF [15]. Figure 1 schematically illustrates the structure and operating principle of the proposed LCF-MZI, which is realized by arc-fusing one LC-infiltrated HOF with length L spliced between two standard single-mode lead-in/lead-out fibers, which act as the input and output ports for light.…”
Section: Operational Principlementioning
confidence: 99%
“…To overcome this bottleneck, we demonstrate a new liquid crystal-infiltrated fiber Mach-Zehnder interferometer (LCF-MZI) sensor, which is realized by splicing a section of LC-filled hollow optic fiber (HOF) between two single mode fibers (SMFs) [15]. We have demonstrated that the transmission spectrum of such a MZI fiber can be governed by thermal-optic characteristics of LC materials (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated MZIs are the key tuning elements in the "optical field-programmable gate array (FPGA)" [6]. MZI LC structures have been presented before in fiber [14]; however, integrated devices are more stable than conventional or fiber MZIs to ambient thermal changes. Integrated MZIs are typically used as phase shifters, but they are becoming important modules (basic structures) for VIS light in (bio-)sensing or metrology.…”
Section: Introductionmentioning
confidence: 99%